A246 DUAL DELETION OF EPITHELIAL BMPR1A/PTEN IN MICE IMPAIRS COLONIC MUCOSA IDENTITY. (1st March 2018) - Pomerleau, V; Babeu, J; Boudreau, F; Perreault, N
Abstract: NOT PUBLISHED AT AUTHOR'S REQUEST Funding Agencies: CIHR